PENERAPAN METODE BOOTSTRAP FINANCING PADA USAHA KECIL DAN MENENGAH DI SURABAYA - Tommy C. Efrata; Christian Herdinata (University of Merdeka Malang, 2012)
Application of bootstrap financing methods had been very popular among small-scale entrepreneurs in Indonesia.This was because their access to capital was still very limited. Although bootstrap financing methodswere used by many entrepreneurs, the risk factors, timing, market share, education, age, and gender was not yetknown. This study aimed to determine whether there was an influence of risk, time, market share, education,age, and gender of the application of bootstrap financing methods. The sample in this study was small andmedium entrepreneurs in the city of Surabaya. The sampling method used was stratified random sampling.The analysis technique used was multiple regression. The results of this study showed that the risk factors,time, age, and gender affected significantly to the application of the bootstrap method significant financing,while the market share and education had no significant effect.